2018
DOI: 10.3390/jpm8020013
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling on an Unselected Solid Tumor Population Reveals a Highly Mutated Wnt/β-Catenin Pathway Associated with Oncogenic EGFR Mutations

Abstract: Oncogenic epidermal growth factor receptors (EGFRs) can recruit key effectors in diverse cellular processes to propagate oncogenic signals. Targeted and combinational therapeutic strategies have been successfully applied for treating EGFR-driven cancers. However, a main challenge in EGFR therapies is drug resistance due to mutations, oncogenic shift, alternative signaling, and other potential mechanisms. To further understand the genetic alterations associated with oncogenic EGFRs and to provide further insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…β-catenin levels were increased in NSCLC cells with oncogenic EGFR mutations, as well as in gefitinib-resistant cells, and inhibition of the Wnt/β-catenin pathway re-sensitised cells to EGFR inhibitors and increased their efficacy in these tumours [5355]. Recently, Jiang et al reported that EGFR -activating mutations in NSCLC co-occurred with mutations in genes participating in most key signalling pathways and biological processes, including receptors of different classes, key regulators involved in genome and epigenome stability, the PI3K–AKT–mTOR pathway, and the TP53/apoptosis pathway [56]. In the study by Jiang et al, many of the Wnt/β-catenin pathway-related genes linked to oncogenic EGFRs were mutated, and there was more variation in the Wnt/β-catenin pathway than in the TP53/apoptosis and PI3K–AKT–mTOR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin levels were increased in NSCLC cells with oncogenic EGFR mutations, as well as in gefitinib-resistant cells, and inhibition of the Wnt/β-catenin pathway re-sensitised cells to EGFR inhibitors and increased their efficacy in these tumours [5355]. Recently, Jiang et al reported that EGFR -activating mutations in NSCLC co-occurred with mutations in genes participating in most key signalling pathways and biological processes, including receptors of different classes, key regulators involved in genome and epigenome stability, the PI3K–AKT–mTOR pathway, and the TP53/apoptosis pathway [56]. In the study by Jiang et al, many of the Wnt/β-catenin pathway-related genes linked to oncogenic EGFRs were mutated, and there was more variation in the Wnt/β-catenin pathway than in the TP53/apoptosis and PI3K–AKT–mTOR pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The Wnt signaling pathway is essential for the survival of stem cells and the maintenance of the regenerative ability of tissues ( 20 ). The basic role of the Wnt/β-catenin pathway in development requires regulatory control at multiple levels, and a deficiency at any level may lead to tumor formation ( 21 ). Previous studies have demonstrated that the proliferation, invasion and epithelial-mesenchymal transition of CCA cells are associated with Wnt/β-catenin signaling ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The deregulations involve hijacking stem cell self-renewal and its multi-lineage differentiation ability. Subsequently, activation of oncogenes leads to adenocarcinoma development [69]. Patients whose tumors are driven by EGFR classical mutations have been shown to respond well to EGFR tyrosine kinase inhibitors (EGFR-TKIs), including Gefitinib, Erlotinib, Afatinib and Osimertinib [1013].…”
Section: Introductionmentioning
confidence: 99%